2017
DOI: 10.1177/0963662517735430
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to evolution among Christians, Muslims and the Non-Religious in Britain: Differential effects of religious and educational factors

Abstract: According to poll results and media reports, Britain has a significant and growing number of creationists. However, little scholarly research has been carried out to explore this phenomenon. We present results from a national survey of 6020 individuals to give a comprehensive picture of contemporary public attitudes to evolution in Britain. Furthermore, we explore the effects of religion and education on attitudes to evolution. Unique to this study, we analyse the effects of attending a religiously affiliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Johnson et al interpret these references to Dawkins as a distinctive facet of British public debate about science and religion. Unsworth and Voas () also focused on Britian, reporting findings from an original nationally representative survey of the public and concluding that the number of creationists in Britain is smaller than previously speculated and that people who identify as having no religion report more support for evolution than those who belong to a religious group.…”
Section: New Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al interpret these references to Dawkins as a distinctive facet of British public debate about science and religion. Unsworth and Voas () also focused on Britian, reporting findings from an original nationally representative survey of the public and concluding that the number of creationists in Britain is smaller than previously speculated and that people who identify as having no religion report more support for evolution than those who belong to a religious group.…”
Section: New Developmentsmentioning
confidence: 99%
“…Other studies found that people are inconsistent in their objections to science (Evans, , ) or separate scientific knowledge from their identity and beliefs (Long, ). While polls on belief in evolution have implied that public positions on evolution and belief are clear and coherent, more nuanced recent surveys have indicated that many Americans and Britons are unsure about their position on evolution, do not have a view, or do not think having correct belief is important (Hill, ; Unsworth & Voas, ).…”
Section: Understanding Science and Accepting Sciencementioning
confidence: 99%
“…Our results support these findings from past research, and suggest future researchers explore how political conservatism and thinking styles may affect attitudes toward evolution in other countries. For example, in Turkey public acceptance of evolution is similar to US (Miller et al, ), and acceptance is negatively related to conservatism (Edis, ), whereas in the Britain, research suggests no relation between political conservatism acceptance of evolution (Unsworth & Voas, ).…”
Section: Discussionmentioning
confidence: 99%
“…The 'Non-Religious' category comprises respondents who do not affiliate with a religious tradition, and attend religious services infrequently or never. This question followed a series of eight Likert-type scale items related to evolution and age of the earth (for details, see Unsworth and Voas, 2018).…”
Section: Samplementioning
confidence: 99%